Thyroid hormones and heart mitochondrial nitric oxide under hypovolemia - Ogonowski, Natalia Soledad (2018)
The aim of the present work was to examine the effect of thyroid state on rat heart mitochondria function during hypovolemia. Sprague-Dawley rats treated with T3 (hyper, 20 μg/100 g body weight) or 0.02% methimazole (hypo, w/v) for 28 days. Hypovolemia was induced by acute hemorrhage. O2 uptake, complex I activity and mitochondrial nitric oxide synthase (mtNOS) protein levels were determined in heart mitochondria. The malate-glutamate-supported state 3 respiration decreased and increased in hypo and hyperthyroid rats, while state 4 respirations did not change. Complex I activity and mtNOS protein levels were decreased in hypothyroid rats even in acute hypovolemia. Hyperthyroidism did not change these parameters. In summary, this study showed, for the first time, interesting findings that heart mitochondrial function is altered during thyroid disorder and acute hypovolemia. Heart mitochondrial nitric oxide, modulating oxygen uptake, may be involved in the adaptative response to assure the cardiomyocytes survives in this experimental condition.